Eco-critical Discourse Analysis of the Indonesian President’s Statement at the 21st Conference of the Parties in Paris - Mansyur, Siti Awaliyah; Iwa Lukmana; Isnendes, Retty; Gunawan, Wawan (REiLA : Journal of Research and Innovation in Language, 2021)
This study investigates the representation of the environmental, ecological, and climate change issue in the Indonesian President’s Joko Widodo statement at the COP21, 2015. The data was taken from the transcript published by the Indonesian Ministry of Environment and Forestry's official website. It is selected according to the popularity of the President and to learn about his ecological view based on the way he represented the country's ecological issue at the global event. The analysis was carried out within an eco-critical discourse analysis framework, which started by investigating the ideology using Fairclough's three-dimensional model. Then, the ideology was judged using the ecolinguistics perspectives proposed by Stibbe (2015a, 2020). The result shows that President Joko Widodo’s ecological-ideology can be regarded as 'prosaic: environmental problem solving', of which this study concludes that his speech can be defined as a 'beneficial discourse' that has to be promoted widely to raise the awareness of language use regarding an environmental issue.